Nexus of Green Transformational Leadership, GHRM, Green Innovation, and Environmental Performance: Insights from SMEs and Social Entrepreneurs in Sri Lanka - Vasudevan, Asokan; Mathushan, Packiyanathan; Nirojan, Jasintha; Opatha, H.H.D.N.P.; Kengatharan, Naveneethakrishnan (Journal of Ecohumanism, 2024)
Green Human Resource Management (GHRM) is a salient investment for firms to stay sustainably competitive and is instrumental in enhancing organisational environmental performance for natural environmental sustainability. While there has been a significant increase in GHRM, there is a lack of academic empirical studies examining the nexus of green transformational leadership, GHRM, green innovation and environmental performance. Nonetheless, the nexus of those variables must be explored in developing countries, especially Sri Lanka. Drawing upon the Ability Motivation Opportunity (AMO) theory and Resource-Based View (RBV) of the firm, this study aims to substantiate that GHRM fosters environmental performance, especially of Small and Medium Enterprises (SMEs), thus yielding them a competitive edge. The study used bibliometric analysis to analyse unstructured data from 86 journal publications from the Scopus database. Subsequently, a research gap was identified, and a conceptual framework was constructed based on the findings. The theoretical framework was confirmed by analyzing data from a sample of 128 small and medium-sized companies (SMEs) and social entrepreneurs in Sri Lanka employing partial least squares structural equation modeling (PLS-SEM). Strong green transformational leadership is required to improve GHRM and environmental performance, raise the caliber of green innovation, and promote environmental performance within small and medium-sized businesses (SMEs), according to the results of the bibliometric study and the application of partial least squares methods.